IT GOVERNANCE AL-QUR’AN VERSUS DESIGN FACTOR PADA COBIT 19: Indonesia - Ima Dwitawati, Ima; shaffitri, Ghina; Fairuza, Muhammad; Silvia, Putri; Syukri, Ichsanul (Journal of Information Technology (JINTECH), 2023)
Abstract: This study aims to analyze three design factors of COBIT 2019 in the management of information technology (IT) and their relationship with the Qur'an. COBIT is a framework that guides organizations in managing and controlling IT to achieve established business objectives. The Qur'an is a sacred book in the beliefs of Muslimsthat provides guidance and ethical values. This study utilizes literature review to analyze the design factors of COBIT 2019 and compare them with the perspective of the Qur'an regarding IT management. Keywords: Al-Qur’an, COBIT 2019, Information Technology Management, Relation. Abstrak: Penelitian ini bertujuan untuk menganalisis tiga design factor COBIT 2019 dalam pengelolaan teknologi informasi (TI) dan relasinya dengan Al-Qur'an. COBIT adalah kerangka kerja yang mengarahkan organisasi dalam mengelola dan mengendalikan TI untuk mencapai tujuan bisnis yang ditetapkan. Al-Qur’an adalah kitab suci dalam keyakinan umat Islam yang menyediakan pedoman dan nilai etika. Penelitian ini menggunakan studi literatur untuk menganalisis design factor COBIT 2019 dan membandingkannya dengan perspektif Al-Qur'an terkait pengelolaan TI. Kata kunci: Al-Qur’an, COBIT 2019, Pengelolaan Teknologi Informasi, Relasi.